Legal Protection for Gig Economy Workers in Southeast Asia: A Comparative Study on Labor Law Enforcement between Indonesia and Singapore - Dyah Rosiana Puspitasari (Jurnal Smart Hukum (JSH), 2027)
The rapid expansion of the gig economy across Southeast Asia has fundamentally disrupted traditional labor market structures, creating a significant regulatory void in the protection of platform workers. This article presents a comparative legal analysis of labor law enforcement for gig economy workers in Indonesia and Singapore, two Southeast Asian nations with distinctly different regulatory approaches. Employing qualitative legal research methodology with a normative-comparative approach, this study examines the statutory frameworks, judicial interpretations, and policy instruments governing platform work in both jurisdictions. The findings reveal a striking regulatory divergence: Singapore has enacted the Platform Workers Act 2024, establishing a sui generis legal category for platform workers with mandatory Central Provident Fund contributions, work injury compensation, and collective representation rights. In contrast, Indonesia continues to rely on fragmented regulations that relegate platform workers to ambiguous "partnership" status, excluding them from basic labor protections under Law No. 13 of 2003 on Manpower. The study identifies that less than 3.5% of Indonesian gig workers possess employment social security, while Singapore provides comprehensive coverage to approximately 70,000 platform workers. This article argues that Indonesia's regulatory inertia constitutes a structural inequality that perpetuates worker vulnerability, and recommends the adoption of a hybrid "third category" legal framework inspired by Singapore's progressive model, while adapting it to Indonesia's unique socio-economic context